Guide to deliver the elements of the Clinical Caritas Process - Luana Tonin; Jaqueline Dias do Nascimento; Maria Ribeiro Lacerda; Luciane Favero; Ingrid Meireles Gomes; Adelita Gonzalez Martinez Denipote (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To introduce a guide to apply the elements of the Clinical Caritas Process. Methods: It is a study introducing a guide developed to identify the necessary caring actions, aiming to provide transpersonal care. It was designed from a bibliographic review and discussion with peers, who apply the theory underpinning the present study. Results: The instrument features a layout with ten lines and two columns, decoding each structural component in its enunciation with its respective care manifestations. Additionally, it showed to be a facilitator for the use of the Human Caring Theory. Conclusion: It is believed that the guide can be reproduced in order to direct the practice of transpersonal care in different settings of Brazilian nursing. Moreover, it can also be used to teach this theory.